Respuesta :
Answer:
x = -6 , -2
Step-by-step explanation:
Find factors of x² and 12, in which, when combined, will give 8x:
x² + 8x + 12 = 0
x 6
x 2
(x + 6)(x + 2) = 0
Check. Use the FOIL method:
First, combine the first terms: x * x = x²
Next, combine the outside terms: x * 2 = 2x
Then, combine the inside terms: 6 * x = 6x
Finally, combine the last terms: 6 * 2 = 12
Combine like terms: x² + (2x + 6x) + 12
x² + 8x + 12
Solve for the solutions. Set each parenthesis equal to 0:
(x + 6)(x + 2) = 0
(x + 6) = 0
(x + 2) = 0
Isolate the variable x. Subtract 6 & 2 from both sides for their respective equation:
x + 6 = 0
x + 6 (-6) = 0 (-6)
x = 0 - 6
x = -6
x + 2 = 0
x + 2 (-2) = 0 (-2)
x = 0 - 2
x = -2
x = -6 , -2
~
Answer: {-6, -2}
Step-by-step explanation: First look if you can factor the left side.
In this case, the trinomial on the left can be factored.
The left side of the equation is a trinomial in a special form
that can be factored as the product of two binomials.
As our first term for each binomial, we will have the factors of x².
Since x² breaks down into x · x, we use an
x in the first position of each binomial.
For our second term, we are looking
for factors of 12 that add to 8.
In this case, these factors are 6 and 2.
So we have (x + 6)(x + 2) = 0.
So either x + 6 = 0 or x + 2 = 0.
Solving each equation from here, we find that x = -6 or x = -2.
We can write our answer as the solution set {-6, -2}.